2017
DOI: 10.1055/s-0043-112344
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Transient Production of a Monoclonal Antibody Neutralizing the Porcine Epidemic Diarrhea Virus (PEDV) in Nicotiana benthamiana and Lactuca sativa

Abstract: Porcine epidemic diarrhea virus (PEDV) causes acute diarrhea, vomiting, dehydration, weight loss, and high mortality rate in neonatal piglets. Porcine epidemic diarrhea (PED) has been reported in Europe, America, and Asia including Thailand. The disease causes substantial losses to the swine industry in many countries. Presently, there is no effective PEDV vaccine available. In this study, we developed a plant-produced monoclonal antibody (mAb) 2C10 as a prophylactic candidate to prevent the PEDV infection. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Previous studies have described tobacco-derived plantibodies that showed potent therapeutic activity against multiple viruses such as EBOV, HBV, HIV, PEDV, RABV, WNV, and others in small animal models of infection, e.g., mice [39,[42][43][44][45][46]. However, to our knowledge, this is the first study demonstrating the ability of plantibodies to protect against influenza viral infections.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Previous studies have described tobacco-derived plantibodies that showed potent therapeutic activity against multiple viruses such as EBOV, HBV, HIV, PEDV, RABV, WNV, and others in small animal models of infection, e.g., mice [39,[42][43][44][45][46]. However, to our knowledge, this is the first study demonstrating the ability of plantibodies to protect against influenza viral infections.…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, plantibodies overcome some of the concerns associated with animal-derived therapeutic MAbs obtained from serum or plasma, including intermediate reactions, pyrogenicity, potential contamination with other zoonotic pathogens and/or toxins, and serum sickness [32,[34][35][36][37]. For these reasons, plantibodies have been proposed for the treatment of several bacterial (e.g., Salmonella, Streptococcus, Porphyromonas) and viral (e.g., Ebola virus, EBOV; Hepatitis B virus, HBV; Human immunodeficiency virus, HIV; Porcine epidemic diarrhea virus, PEDV; Rabies virus, RABV; West Nile virus, WNV) infections or toxins (e.g., ricin and shiga toxin) [35,[38][39][40][41][42][43][44][45][46]. However, to date, plantibodies have not been used for the treatment of influenza viral infections.…”
Section: Introductionmentioning
confidence: 99%
“…Efficient complex formation is required to produce antibodies in plant cells. It has previously been shown that non-competing amplification of two different replicons can be achieved using a geminiviral replication vector (Phoolcharoen et al, 2011;Diamos et al, 2016;Rattanapisit et al, 2017). The most renowned and widely used transient expression system is the magnICON system (Marillonnet et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Plants have been used to produce a variety of recombinant proteins, such as monoclonal antibodies, vaccines, therapeutic proteins, enzymes, etc. [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%